Metabolite-Mediated Protein Macrocyclization - Paikin, Zachary E.; Galindo, Ana Villalobos; Raj, Monika (Synlett, 2025)
Protein macrocyclization is a pivotal process in the stabilization of protein structures, significantly enhancing their proteolytic stability and thermostability. While nature elegantly accomplishes this through a diverse family of ligases, laboratory methods typically rely on recombinant proteins engineered with unnatural amino acids and cysteine crosslinkers. Herein, we present a biological metabolite 4-hydroxynonenal (4-HNE) to selectively modify nucleophilic amino acids, cysteine (Cys), histidine (His), and lysine (Lys) into electrophilic hemiacetals followed by cyclization via oxime chemistry. This reaction demonstrates a broad substrate scope, enabling the modification and cyclization of proteins with a wide range of three-dimensional structures and molecular weights, from 5.8 to 60 kDa. The resulting cyclized proteins exhibit greater proteolytic stability and enhanced thermal stability at elevated temperatures compared to their uncyclized counterparts. This clearly underscores the critical role of cyclization in preserving the intricate 3D structures of proteins and opens new avenues for advanced protein engineering.
Keywords: proteins; cyclization; chemoselectivity; biomimetic synthesis; bioorganic; chemistry